A TRANSITIONAL ANALYSIS OF ONLINE EDUCATION: A CUSTOMIZE AND FLEXIBLE APPROACH IN INDIA 3-DECADE ANALYSIS - Homavazir, Zuleika; Dikshit, Sukanya; Gambhir, Vinima; Homavazir, Malcolm (Education and Society, 2023)
E-learning is expected to be the future of education. This paper deals with the concerns that it entails and the development and growth that e-learning offers to India. The country's dark realities of severe economic muddles and discriminatory affairs make it exclusive to the privileged. The major stakeholders, the students, are facing immense changes with education as it transitions from the traditional face-to-face method to online platforms, be it in terms of their mental and physical health, all-around development, or their missing out on a wholesome learning experience which involves interacting with peers daily. Further, the traditional approaches in Indian pedagogy have clashing views and difficulties adapting to online education. Not just them, but the virtualization of education affects a large portion of society, whether in the civil or commercial sectors. The necessity for the Indian educational ecosystem to compete with the world's rapidly developing educational technology industry is intertwined with the country's economic and social development. The article also demands e-learning as a social investment and indicates that e-learning government policies are the factors that exclusively dictate the future of e-learning. The primary goal of this research paper is to comprehend the notion of e-learning and to investigate the many types of e-learning. It also highlights many points of view on the contrast of old and modern learning techniques. Modern methods of teaching and learning are beneficial to the growth of the education sector in India. The study report focuses on classroom learning and e-learning in India as a major wheel of educational progress.
ISME
Keywords: Transitional analysis; online education; customised approach; flexible approach.